If You're a Critical Theorist, How Come You Work for a University?. Issue 3 (3rd July 2018) - Loick, Daniel
ABSTRACT: How can we deal with the apparent contradiction between the normative ideals of critical theory and the practice of the current university system? To answer this question, I consult three classical criticisms of the university system: At the beginning of the nineteenth century, the French educator Joseph Jacotot formulated a pedagogical critique of the disciplinary effects of the educational system; at the beginning of the twentieth century, German historian Franz Rosenzweig articulated an ethical critique of the hegemonic educational system's distance from life; and at the beginning of the twentyfirst century, British feminist Sara Ahmed proposed a political critique of the oppressing functions of academic institutions. Taken together, these critiques can serve as an orientation for critical intellectual practice even within the academic system. Finally, I try to describe the relation between critical theory and the university thus evolving by utilising Stefano Harney's and Fred Moten's concept of the "undercommons".